Association Between Oral Microbiota and Cigarette Smoking in the Chinese Population - Jia, Yi-Jing; Liao, Ying; He, Yong-Qiao; Zheng, Mei-Qi; Tong, Xia-Ting; Xue, Wen-Qiong; Zhang, Jiang-Bo; Yuan, Lei-Lei; Zhang, Wen-Li; Jia, Wei-Hua (Frontiers in Cellular and Infection Microbiology, 2021)
The oral microbiota has been observed to be influenced by cigarette smoking and linked to several human diseases. However, research on the effect of cigarette smoking on the oral microbiota has not been systematically conducted in the Chinese population. We profiled the oral microbiota of 316 healthy subjects in the Chinese population by 16S rRNA gene sequencing. The results showed that smokers had significantly a higher Shannon diversity index than never smokers (P = 0.002). Several bacterial taxa were first reported to be associated with cigarette smoking by LEfSe analysis, including Moryella (q = 1.56E-04), Bulleidia (q = 1.65E-06), and Moraxella (q = 3.52E-02) at the genus level and Rothia dentocariosa (q = 1.55E-02), Prevotella melaninogenica (q = 8.48E-08), Prevotella pallens (q = 4.13E-03), Bulleidia moorei (q = 1.79E-06), Rothia aeria (q = 3.83E-06), Actinobacillus parahaemolyticus (q = 2.28E-04), and Haemophilus parainfluenzae (q = 4.82E-02) at the species level. Two nitrite-producing bacteria that can increase the acidity of the oral cavity, Actinomyces and Veillonella, were also enriched in smokers with FDR-adjusted q-values of 3.62E-06 and 1.10E-06, respectively. Notably, we observed that two acid production-related pathways, amino acid-related enzymes (q = 6.19E-05) and amino sugar and nucleotide sugar metabolism (q = 2.63E-06), were increased in smokers by PICRUSt analysis. Finally, the co-occurrence analysis demonstrated that smoker-enriched bacteria were significantly positively associated with each other and were negatively correlated with the bacteria decreased in smokers. Our results suggested that cigarette smoking may affect oral health by creating an acidic environment by altering bacterial abundance, connections among oral microbiota, and the microbiota and their metabolic function.